2020
DOI: 10.1039/d0fo01219j
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous natural EPA-enriched phosphatidylcholine and phosphatidylethanolamine ameliorate lipid accumulation and insulin resistance via activation of PPARα/γ in mice

Abstract: Dietary eicosapentaenoic acid in the form of phosphatidylcholine and phosphatidylethanolamine improves lipid accumulation and insulin resistance via activation of PPARα/γ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Therefore, we subsequently analyzed the fatty acid composition in the femur, and the results showed that the DHA content in the femur of the DHA-PC group, DHA-TG group, and DHA-EE group was 3.86, 2.66, and 2.22%, respectively (Table ), which is consistent with Che et al’s results in high-fat fed mice . Besides, Tian et al demonstrated that EPA-PC could be a dual-selective agonist of PPARα/γ . There is substantial evidence documenting that PPARγ plays a key role in bone homeostasis.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Therefore, we subsequently analyzed the fatty acid composition in the femur, and the results showed that the DHA content in the femur of the DHA-PC group, DHA-TG group, and DHA-EE group was 3.86, 2.66, and 2.22%, respectively (Table ), which is consistent with Che et al’s results in high-fat fed mice . Besides, Tian et al demonstrated that EPA-PC could be a dual-selective agonist of PPARα/γ . There is substantial evidence documenting that PPARγ plays a key role in bone homeostasis.…”
Section: Discussionsupporting
confidence: 84%
“…Mao et al showed that DHA-PC promoted MSC differentiation into osteoblasts over adipocytes by regulating PPARγ. 45,46 Wang also demonstrated that DHA-PC could protect chondrocytes from apoptosis through activating PPARγ. 47 Moreover, Chakravarthy et al identified PC as a physiologically relevant endogenous PPARα ligand.…”
Section: ■ Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A previous study found that dietary PC was mainly hydrolyzed to 1-lyso-PC, which was effectively absorbed and reacylated to PC or degraded to glycerophoshocholine GPC , glycerophosphate and free choline 35 . Although dietary EPA-PC and EPA-PE can change the composition of fatty acids in the blood 36 , the brain is a closed system isolated by the blood-brain barrier, and supplementation of exogenous lipids may not cause significant changes in the composition of brain lipids.…”
Section: Pufa Content In Glycerophospholipidsmentioning
confidence: 99%